PENGARUH CITRA MEREK, HARGA, INOVASI DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PADA KOSMETIK WARDAH DI KOTA LANGSA - Cut Liza Fadhila; Dewi Rosa Indah; Safrizal (Jurnal Mahasiswa Akuntansi Samudra, 2022)
This study aims to examine the effect of brand image, price, innovation and product quality on customer loyalty at Wardah cosmetics in Langsa City. The data analysis method used is multiple linear regression analysis method. The population in this study were all Wardah consumers in Langsa City with an unknown population and the sample used was 96 respondents. The sampling technique used is non-probability sampling with purposive sampling method. The multiple linear regression analysis equation obtained is Y = 28,933 + 0,068X1 + 0,072X2 + 0,052X3 + 0,055X4. The constant value of 28.933 is the value of customer loyalty if the variable X is fixed. Variables X1 and X2 have a negative effect on Y, while X3 and X4 have a positive effect on Y. The results of the t-test of the X1 variable have a value of 0.049 <0.05, which means that the X1 variable has a significant effect on Y, the X2 variable has a value of 0.050 <0.05, which means that the X2 variable has a significant effect. on Y, the X3 variable has a value of 0.062 > 0.05, which means that the X3 variable has no significant effect on Y, and the X4 variable has a value of 0.000 < 0.05, which means that the X4 variable has a significant effect on Y. The F test results obtained a value of 0.001 < 0.05 which indicates that the variable used significant effect on Y. The coefficient of determination test results obtained a value of 14.3% and the remaining 85.7% is influenced by other factors not examined in this study.